THE EFFECTIVENESS OF CELEBRITY ENDORSEMENT ON PURCHASING: A STUDY AMONG UNIVERSITY OF GHANA STUDENTS - CHIMSAH, MILLICENT SAMIRAH (2016)
Celebrities from sports or movies make an impact in advertising. This study uncovers the effectiveness of celebrity endorsements on purchasing with specific objectives set to examine the impact of celebrity endorsement on the buying decisions of students and to identify factors that influence effectiveness of celebrity endorsements. A total of 14 students were sampled from the Psychology Department of University of Ghana using the convenience sampling technique. The study employed a qualitative approach, which was conducted through the use of interviews. Thematic analysis revealed three major themes, which were: perceived reasons why celebrities are used for endorsements, qualities of celebrities’ endorsers and effectiveness versus ineffectiveness. It was found that some of the participants do not watch television and do not like celebrities in advertisements. On this basis, analysis was done recommendations are discussed.